Optimizing chromium removal from synthetic wastewater via electrocoagulation process with a natural coagulant (blended of eggshell powder and lime) using response surface methodology - Firomsa Bidiraa; Endrias Adane Bekele; Werkne Sorsa Muleta (Heliyon)
The presence of chromium (Cr) in synthetic wastewater has become a serious environmental issue. Therefore, main aim of this work was to investigate Cr removal from synthetic wastewater via electrocoagulation (EC) with a natural coagulant using aluminum electrodes. The central composite design (CCD) of the response surface methodology (RSM) method was used to optimized the operating variables of solution pH (5–9), initial Cr concentration (225–475 mgL-1), reaction time (30–40 min), and applied current (0.35–0.55 A). The ANOVA results clearly shows that the quadratic model (p < 0.0001) was sufficient to the best predicting of the removal performance of Cr (R2 = 0.9994 for electrode distance of 0.5 cm and 0.9924 for 1 cm). The maximum removal (99.836 % for electrode distance of 0.5 cm, and 98.175 % for 1 cm) of Cr was achieved with optimized conditions of solution pH 7.053, initial Cr concentration 337.795 mgL−1, reaction time 37.148 min, and applied current of 0.505 A. From this finding, it was proved that the EC process assisted with natural coagulant is an efficient, and cost-effective method for the removal of Cr from synthetic wastewater.